SELF-CONTROL, SOCIAL PRESSURE, AND THE PREVENTION OF ONLINE GAMBLING AMONG MUSLIM UNIVERSITY STUDENTS - Muhammad Arqam; Nenik Woyanti (BISECER (Business Economic Entrepreneurship), 2026)
The development of digital technology has increased accessibility to online gambling and has transformed it into a serious socio-economic issue. Muslim university students in Jakarta are considered a relevant group, as they represented a population with high internet penetration while simultaneously being guided by Islamic teachings that prohibit gambling practices. This study aims to analyze the effect of self-control, Islamic financial literacy, income, and peer pressure on the prevention of online gambling behaviour among Muslims university students in Jakarta. This research adopt a quantitative approach with survey method involving 100 respondents. The results indicate that, simultaneously, self control, Islamic financial literact, income, and peer pressure have a significant effect on the prevention of online gambling behaviour. Partially, self control, income, and peer pressure show a significant and negative effect, while Islamic financial literacy does not demonstrate a significant effect. These findings suggest that the prevention of online gambling behaviour is influenced not only by internal factors but also by economic condition and social environment. This study emphasizes the importance of multidimensional preventive approach that incorporates both the strengthening of a healthy social environment and enhancement of individual awareness.